Clinical characteristics and factors related to infection with SCCmec type II and IV Methicillin-resistant Staphylococcus aureus in a Japanese secondary care facility: a single-center retrospective study. (December 2022) - Nakano, Yuki; Murata, Masayuki; Matsumoto, Yuji; Toyoda, Kazuhiro; Ota, Azusa; Yamasaki, Sho; Otakeno, Hisao; Yokoo, Kenjo; Shimono, Nobuyuki
Highlights: SCC mec type IV MRSA was prevalent in our hospital, but not as traditionally defined. The proportion of psm-mec mutation in SCC mec type II MRSA harboring seb was 89%. SCC mec type IV MRSA harbored sea and cna (83%) but not PVL genes ( lukF-PV / lukS-PV ). SCC mec type IV MRSA causes severe conditions and frequent bloodstream infections. Infection factors were psm-mec mutation (type II MRSA), sea and cna (type IV MRSA). Abstract: Objectives: Differences in virulence genes, including psm-mec, which is a phenol-soluble modulin-mec (PSM-mec) encoding gene, of predominant staphylococcal cassette chromosome mec (SCC mec ) types II and IV Methicillin-resistant Staphylococcus aureus (MRSA) may contribute to the virulence and clinical features of MRSA in Japan. We aimed to clarify the clinical characteristics and risk factors of infection among SCC mec types II and IV MRSA isolates from a Japanese secondary acute care hospital. Methods: We analysed 58 SCC mec type II and 83 SCC mec type IV MRSA isolates collected from blood, central venous catheter tips, deep or superficial tissues, and sputum. Results: SCC mec type II MRSA risk factors for progression to infection were seb, enterotoxin gene cluster, psm-me c mutation, and vancomycin minimum inhibitory concentrations (MIC) of 1 or 2 mg/L as virulence factors (adjusted odds ratio [aOR] = 11.8; 95% confidence interval [CI]: 2.49–77.7; P  = 0.004); solid tumour was a host factor (aOR = 25.9; 95% CI: 3.66–300; P  = 0.003). SCC mec type IV MRSA risk factors were sea, cna, and vancomycin MIC of 1 or 2 mg/L as virulence factors (aOR = 3.14; 95% CI: 1.06–10.6; P  = 0.049) and intravascular indwelling catheter as host factors (aOR = 3.78; 95% CI: 1.03–14.5; P  = 0.045). Compared with SCC mec type II, SCC mec type IV MRSA resulted in more frequent bloodstream infections and higher Sequential Organ Failure Assessment scores. Conclusion: We found that factors related to virulence genes and bacteriological and host characteristics are associated with SCC mec types II and IV MRSA infection and severity. These risk factors may be useful criteria for designing infection control programs.